1984
DOI: 10.1029/jb089ib06p04125
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional crack healing in quartz

Abstract: Annealing fractured single crystal quartz in the presence of pore fluid at 200 MPa (2 kb) pressure at 400° and 600°C for various periods resulted in the reorganization of initially planar cracks into arrays of spherical and tubular fluid inclusions, a process termed crack healing. Samples heated to 600°C for several days with no added pore fluid showed no optically measurable crack healing. The amount of healing in samples with added pore fluids is a function of the temperature, time, initial concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(145 citation statements)
references
References 31 publications
3
139
0
3
Order By: Relevance
“…C [Smith and Evans, 1984;Laubach, 1989]. The minimum depth of healing in the present study, D h , is estimated to be at least 1 km, assuming that the geothermal gradient is 50-100 C/km in the study area [Tanaka et al, 1999]; OF would have formed at a shallower depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C [Smith and Evans, 1984;Laubach, 1989]. The minimum depth of healing in the present study, D h , is estimated to be at least 1 km, assuming that the geothermal gradient is 50-100 C/km in the study area [Tanaka et al, 1999]; OF would have formed at a shallower depth.…”
Section: Discussionmentioning
confidence: 99%
“…Based on cross-cutting relationships between microfracture types, we suggest that HF is older than OF. HF observed in the damage zone was previously OF before becoming a healed plane of secondary fluid inclusions due to the local-scale diffusive transport of the constitutive atoms in the crystallizing minerals [Smith and Evans, 1984]. Experimental and field studies have shown that microfracture healing likely occurs at ambient temperatures above~100…”
Section: Discussionmentioning
confidence: 99%
“…6). We know little of this early brittle deformation, but these fluid inclusion arrays have microstructures similar to those generated during hydrothermal diffusional healing of cracks (Smith and Evans, 1984;Beeler and Hickman, 2015). As a result, early brittle deformation, infiltration of water along open cracks, and crack healing appear to be important to the early introduction of water to quartz grain interiors (Kronenberg et al, 1986FitzGerald et al, 1991;Diamond et al, 2010;Tarantola et al, , 2012Stünitz et al, 2017).…”
Section: Wide Variations In Oh Contentmentioning
confidence: 99%
“…For a pegmatite sheet of a thickness in the range of decimetres the thermal perturbation may have a life-time of a couple of weeks before the maximum temperature in the centre of the vein has dropped to nearly the pre-intrusive host rock temperature. Experimental studies on healing of microcracks (Smith and Evans, 1984) have revealed that the healing rate is strongly dependent on temperature. At temperatures of 300 8C, healing of microcracks in quartz is predicted to be a matter of days to weeks, and at higher temperatures it may proceed quasi-instantaneously when compared with geological time scales.…”
Section: Infiltration Of Fluid Into the Damaged Host Rock And Lifetimmentioning
confidence: 99%